2019
DOI: 10.1186/s13048-019-0601-6
|View full text |Cite|
|
Sign up to set email alerts
|

Kallistatin inhibits tumour progression and platinum resistance in high-grade serous ovarian cancer

Abstract: Ovarian cancer is the most lethal gynaecologic malignancy. Although there are various subtypes of ovarian cancer, high-grade serous ovarian cancer (HGSOC) accounts for 70% of ovarian cancer deaths. Chemoresistance is the primary reason for the unfavourable prognosis of HGSOC. Kallistatin (KAL), also known as SERPINA4, is part of the serpin family. Kallistatin has been discovered to exert multiple effects on angiogenesis, inflammation and tumour progression. However, the roles and clinical significance of kalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, BCL7A expression was negatively correlated with glioma grades. These results strongly suggest that BCL7A is a potential novel tumor suppressor gene in glioma, similar findings were reported previously [ 26 ]. We also investigated the prognostic role of BCL7A for the first time in glioma.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, BCL7A expression was negatively correlated with glioma grades. These results strongly suggest that BCL7A is a potential novel tumor suppressor gene in glioma, similar findings were reported previously [ 26 ]. We also investigated the prognostic role of BCL7A for the first time in glioma.…”
Section: Discussionsupporting
confidence: 92%
“…Elsewhere, ovarian cancer (OC) patients with high expression of BCL7A had shorter overall survival (OS) /progression-free survival (PFS) than those with low levels of BCL7A. BCL7A expression was implicated as an independent risk factor for poor prognosis OC patients [ 26 ]. Consistent with the role of BCL7A in OC, we identified BCL7A as a novel prognostic biomarker for LGG patients and GBM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Test classification was also shown to be associated with expression of complement C2, complement factor B, RBP4, kallistatin, C9, CRP, insulin-like growth factor-binding protein 1 (IGF-1), and D-dimer. Association of these proteins with prognosis in cancer, in general, and EOC, in particular, has been observed in previous studies [37][38][39][40][41][42][43]. In this regard, meta-analyses demonstrated that high CRP levels were associated with increased risk of invasive EOC [38], whereas no significant association of IGF-1/IGFBP-3 with EOC risk was identified [39].…”
Section: Discussionmentioning
confidence: 58%
“…In this regard, meta-analyses demonstrated that high CRP levels were associated with increased risk of invasive EOC [38], whereas no significant association of IGF-1/IGFBP-3 with EOC risk was identified [39]. In addition, RBP4 was shown to drive ovarian cancer cell migration [40]; pretreatment plasma D-dimer levels were associated with chemoresistance and poor disease outcome [41,42]; and low expression of kallistatin was associated with unfavorable prognosis, platinum resistance, and relapse [43]. These results indicate a potential relation to the individual immunological host-response to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further to elucidate the chemotherapy resistance mechanism of HGSOC is of great signi cance to reduce chemotherapy resistance and improve the prognosis of HGSOC patients. Our group has focused on chemo-resistance of ovarian cancer for many years [3][4][5]. Recent years, the role of tumor microenvironment in chemoresistance of ovarian cancer has aroused our interest.…”
Section: Introductionmentioning
confidence: 99%